2017
DOI: 10.1017/s0022149x16000912
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete mitochondrial genome of Setaria digitata (Nematoda: Setariidae) from China

Abstract: Setaria digitata is a filarial parasite that causes fatal cerebrospinal nematodiasis in goats, horses and sheep, resulting in substantial economic losses to livestock farmers. In the present study, the complete mitochondrial (mt) genome of S. digitata from China was determined, characterized and compared with that of S. digitata from Sri Lanka. The identity of the mt genomes was 98.3% between S. digitata from China and Sri Lanka, and the complete mt genome sequence of S. digitata from China was slightly shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Gel electrophoresis produced a 209 bp band, and the sample was confirmed as S. digitata when compared against other sequences in the NCBI GenBank database using BLAST. The genetic sequence extracted from the worm was 99% similar to that of S. digitata isolated from cattle and buffalos in Sri Lanka and from buffalos in China [20,21]. The mind-point rooted phylogenetic tree further confirmed that the S. digitata isolated from this study belongs to the same major clade isolated from Japan, India and Sri Lanka.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Gel electrophoresis produced a 209 bp band, and the sample was confirmed as S. digitata when compared against other sequences in the NCBI GenBank database using BLAST. The genetic sequence extracted from the worm was 99% similar to that of S. digitata isolated from cattle and buffalos in Sri Lanka and from buffalos in China [20,21]. The mind-point rooted phylogenetic tree further confirmed that the S. digitata isolated from this study belongs to the same major clade isolated from Japan, India and Sri Lanka.…”
Section: Resultssupporting
confidence: 69%
“…Therefore, this finding suggests that cattle in northern China may carry S. digitata, and further investigation of its prevalence will be worthwhile. In 2017, S. digitata was first identified by molecular method in the cadavers of buffalos in southern China, yet not in live buffalos or cattle [21]. Setariasis is a well-recognized ophthalmological disorder in equine, with S. digitata being reported as the most common cause [27].…”
Section: Resultsmentioning
confidence: 99%
“…The analyses of several hundred mosquitoes collected in Cambodia, Mali, Guinea and Maryland revealed well-known human pathogens including P. falciparum, which was the target of the initial study of the Cambodian samples (24). In addition, we detected Theileria species and Setaria digitata, which cause livestock diseases in Southeast Asia (38)(39)(40)(41)(42). While we were initially unable to conclusively determine the exact Theileria species with our initial assay, targeted follow-up studies using longer amplicons and Sanger sequencing (Figure 2) revealed that the sequences amplified from the African mosquitoes were most closely related to T. velifera and T. mutans, which are both known to infect African cattle (43), whereas the Cambodian mosquitoes carried sequences most closely related to T. sinensis, a species that infects cattle in China (44).…”
Section: Discussionmentioning
confidence: 94%
“…The analyses of several hundred mosquitoes collected in Cambodia, Mali, Guinea and Maryland revealed well-known human pathogens including P. falciparum, which was the target of the initial study of the Cambodian samples (24). In addition, we detected Theileria species and Setaria digitata, which cause livestock diseases in Southeast Asia (38)(39)(40)(41)(42). While we were initially unable to conclusively determine the exact Theileria species with our initial assay, targeted follow-up studies using longer amplicons and Sanger sequencing (Figure 2) revealed that the sequences amplified from the African mosquitoes were most closely related to T. velifera and T. mutans, which are both known to infect African cattle (43), whereas the Cambodian mosquitoes carried sequences most closely related to T. sinensis, a species that infects cattle in China (44).…”
Section: Biology Open • Accepted Manuscriptmentioning
confidence: 94%